ZGT 374E/3 - Remote Sensing - February - March 2005 - PPSF, Pusat Pengajian Sains Fizik (2005)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2004/2005 February - March 2005 ZGT 374E/3 - Remote Sensing [Penderiaan Jauh] Duration: 3 hours [Masa: 3 jam]